'Undivided' city in a divided society: explaining the peaceful coexistence of Albanians and Serbs in Kamenicë/Kamenica, Kosovo. - Djordjević, Andjela; Zupančіč, Rok (Journal of Southeast European & Black Sea Studies, 2025)
The goal of this paper is to examine which factors have influenced interethnic relations between Albanians and Serbs in Kamenicë/Kamenica, which is significantly less hostile compared to other towns in Kosovo. Utilizing a multi-method research approach, we find these factors include historical-demographic, geopolitical, institutional, economic and cultural factors, as well as the work of the members of the international peacebuilding and peacekeeping missions deployed in the municipality of Kamenicë/Kamenica in June of 1999. Based on our findings, the concept of local-local hybridization is proposed as the main theoretical contribution to the theory of hybrid peace. This concept entails long-lasting interactions between ethnic groups in a local (post-conflict) community under different social circumstances and factors that affected their coexistence, whereby this must be supported by peacebuilding and peacekeeping activities adapted to the aforementioned concept if peace is to be sustained.